Enhancement of zinc availability and yield performance of black gram (Vigna mungo L.) through zinc solubilizing bacteria in alkaline soils - Prabhaharan, J; Uma Sankareswari , R; Veeraputhiran, R; Indirani, R; Kumutha, K; Niharika, P; Suriya, K; Sampath, K T (Plant Science Today, 2025)
The present study investigated the combined effects of zinc sulphate (ZnSO₄) and zinc solubilizing bacteria (ZSB) on black gram (Vigna mungo L.) growth and productivity in alkaline soils. Field experiments were conducted at two locations (Agricultural College and Research Institute, Madurai and Coastal Saline Research Centre, Ramanathapuram) during January 2022 using a randomized block design with eight treatments and three replications. The treatments included varying levels of ZnSO₄ (12.5, 18.75 and 25 kg ha-1) with and without ZSB (500 mL ha-1). Results showed that the combined application of ZnSO₄ (25 kg ha-1) and ZSB (500 mL ha-1) along with soil test-based NPK significantly enhanced plant growth parameters, including plant height (35.4 cm), shoot length (38.18 cm) and root nodules (27.4 per plant). This treatment also recorded the highest seed yield (851 kg ha-1), DTPA-extractable zinc (1.72 mg kg-1) and zinc uptake (84.73 g ha-1). The second most effective treatment was ZnSO₄ at 18.75 kg ha-1 with ZSB, which demonstrated comparable results and superior zinc use efficiency. The study concluded that integrating ZSB with optimal ZnSO₄ doses offers an effective strategy for improving black gram productivity and zinc nutrition in alkaline soils.